Magnitude and associated factors of repeat induced abortion among reproductive age group women who seeks abortion Care Services at Marie Stopes International Ethiopia Clinics in Addis Ababa, Ethiopia - Bethelihem Alemayehu; Adamu Addissie; Wondimu Ayele; Sisay Tiroro; Demelash Woldeyohannes (BMC, 2019)
Abstract Background Repeated induced abortion is important public health concern both in the developing and developed world that increases maternal morbidity and mortality. The aim of this study was to determine the magnitude and associated factors of repeated induced abortion among abortion care service seekers at Marie Stopes International Ethiopia clinics in Addis Ababa, Ethiopia. Methods A cross sectional study was conducted among 429 women seeking abortion care at Marie Stopes International Ethiopia clinics. Simple random sampling technique was used to select study participants. Data were collected by trained data collectors using pretested structured questionnaires. Data were checked for completeness, consistency, coded and entered and analyzed through SPSS version 20. Bivariate and multivariate logistic regression analysis was computed to test the strength of association and the p-value < 0.05 was considered as statistical significant. Result The magnitude of repeat induced abortion was 33.6%. Based on this study age groups 20-24 years (AOR = 1.2; CI: 1.1-2.3), 25-29 years (AOR = 5.4; CI: 3.1-6.2) and 30-34 years (AOR = 1.1; CI: 1.02-2.6); respondents with the educational level of primary (AOR = 0.2; CI: 0.070.6), secondary (AOR = 0.4; CI: 0.2-0.8) and college diploma and above (AOR = 0.4; CI: 0.2-0.6); those with the monthly income of 1001-2000 Ethiopian birr (AOR = 4.2; CI: 1.8-9.4) and 2001-3000 Ethiopian birr (AOR = 0.3; CI: 0.2-0.9); those with years in marriage with 1-2 years (AOR = 2.4; CI: 1.2-4.9) and those with last time of abortions of 1-2 years, 2-3 years and above 3 years, (AOR = 0.2; CI: 0.1-0.5), (AOR = 0.1; CI: 0.05-0.4), (AOR = 0.4; CI: 0.2-0.9), respectively were found to be significantly associated with repeat induced abortions. Conclusion and recommendation The magnitude of repeat induced abortion is similar with the reports from developing countries but it was lower than that of developed countries. Age group (20-24, 25-29 and 30-34 were positively associated with repeat induced abortion), educational level (primary, secondary and collage diploma and above were negatively associated with repeat induced abortion), monthly income (earn 1001-2000 Ethiopian birr were positively where as monthly income between 2001 and 3000 Ethiopian birr negatively associated), years in marriage (1-2 years was negatively associated) and time of last abortion (1-2 years, 2-3 years and above the three years were negatively associated) were the associated factors for repeat induced abortion. Health promotion messages are needed to focus to improve the knowledge of women about contraceptives as a primary prevention of repeated induced abortion.